A Study of politeness strategies used by mcs and guests in “ellen: the ellen degeneres show” and “the tonight show with thanh” - Trương Thị Thu Trang (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2024)
This study aims to examine the types of politeness strategies used by the MCs and the guests in two talk shows “Ellen: The Ellen DeGeneres Show” and “The Tonight Show with Thanh” and as well as the factors influencing their choice in politeness strategies. The data from this study was collected from the utterances of the two MCs and guests in both shows and analyzed under qualitative and quantitive approaches. Based on Brown and Levinson (1987) ‘s theory, the study figured out 1045 samples which included four politeness strategies namely bald on record, positive politeness, negative politeness and off record. The most common strategy in the two shows was positive politeness strategy and the least popular one was off record. In the case of Ellen show, the occurrences of bald on record followed the positive politeness (bald on record 15.5% and positive politeness strategy: 67,62%) while in The Tonight Show with Thanh, negative politeness went after positive politeness (positive politeness strategy: 52.36 % and negative politeness strategy: 40,69%). According to the study, the host and the guests in the Vietnamese show tended to use positive and negative politeness, whereas American speakers were more direct than Vietnamese speakers because they used more imposing strategies.